CuBr-лазер с пониженным энерговкладом в разряд; Квантовая Электроника; Т. 30, № 5 - Евтушенко Г. С. Геннадий Сергеевич; Петраш Г. Г.; Суханов В. Б. Виктор Борисович; Федоров В. Ф.; Шиянов Д. В. Дмитрий Валерьевич (2000, 2000)
Заглавие с экрана